1991
DOI: 10.1002/jbmr.5650060711
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for nonrenal synthesis of 1,25-dihydroxyvitamin d in patients with inflammatory arthritis

Abstract: The extrarenal synthesis of 1,25-dihydroxyvitamin D [1,25-(OH)2D] is a characteristic of activated macrophages and has been demonstrated to occur in vitro in synovial fluid macrophages from patients with inflammatory arthritis. To examine whether such synthesis occurs in vivo, 19 patients with rheumatoid arthritis, 5 patient controls, and 5 healthy controls received a challenge oral dose of 250 micrograms 25-hydroxyvitamin D3 (25-OHD3) and the serum 1,25-(OH)2D3 response was measured. The median rise in serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 31 publications
2
29
1
1
Order By: Relevance
“…Instead, the 1,25(OH)2D3 molecules produced in these tissues act through intracrine and paracrine mechanisms to regulate VDRdependent activities of the local cells. However, excessive production of 1,25(OH)2D3 in extrarenal tissues can result in spilling over of 1,25(OH)2D3 to the blood circulation, thus raising blood levels of 1,25(OH)2D3, which in turn can cause hypercalcemia [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Therefore, extrarenal production of 1,25(OH)2D3 can have deleterious consequences, such as the development of acute pancreatitis as discussed below.…”
Section: Vitamin D Metabolism In Extrarenal Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, the 1,25(OH)2D3 molecules produced in these tissues act through intracrine and paracrine mechanisms to regulate VDRdependent activities of the local cells. However, excessive production of 1,25(OH)2D3 in extrarenal tissues can result in spilling over of 1,25(OH)2D3 to the blood circulation, thus raising blood levels of 1,25(OH)2D3, which in turn can cause hypercalcemia [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Therefore, extrarenal production of 1,25(OH)2D3 can have deleterious consequences, such as the development of acute pancreatitis as discussed below.…”
Section: Vitamin D Metabolism In Extrarenal Tissuesmentioning
confidence: 99%
“…Given that inflammation in various tissues is a major cause of extrarenal synthesis of 1,25(OH)2D3 [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], it is not surprising that epidemiological studies have found high incidence of acute pancreatitis in patients with rheumatoid arthritis or systemic lupus erythematous disease [49][50][51][52].…”
Section: Hypercalcemia and Acute Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…45 Confirmation of this observation has been demonstrated in Crohn's disease 46 and rheumatoid arthritis, 44 with Kavathia et al tying higher levels of 1,25-D to greater disease severity in sarcoidosis patients, 47 and Mawer et al finding that 1,25-D levels were particularly elevated in the synovial fluid surrounding the joints of subjects with rheumatoid arthritis. 48 We have previously predicted, based on molecular in silico emulation, that at higher concentrations, 1,25-D interferes with expression of several of the body's other key nuclear receptors, including the glucocorticoid receptor, the androgen receptor and the thyroid receptor. 49 These receptors also express various families of AmPs-20, 17 and 15 families, respectively, out of the 22 analyzed by Brahmachary.…”
Section: Communities Of Microbes Drive Autoimmune Diseasementioning
confidence: 99%